Pengembangan Penanaman Nilai-Nilai Islam: Pembelajaran Bahasa Arab untuk Anak-Anak TPA Masjid Jami’ Al Faidah Gading Asri - Muttaqin, Iqbal; Ahyarudin, Ahyarudin; Lubis, Mhd. Ryza Setiadi; Alwi, Ahmad; Pratama, Bagus (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
Arabic is one of the essential elements in Islamic education as it is the primary language of the Qur'an and Hadith. Understanding Arabic not only helps Muslims read and comprehend religious texts but also plays a role in character development through the appreciation of moral values embedded within. This journal aims to explore effective methods for teaching Arabic to children, particularly in the TPA (Qur'anic Learning Centers), using fun and interactive approaches. The results show that practice-based learning can enhance children's interest and ability in acquiring basic Arabic skills. Therefore, this program is expected to be a significant first step in shaping a knowledgeable and virtuous Muslim generation.